Kaikovus' work "Kabusnoma" is the upbringing of a spiritually mature generation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is one of today's urgent problems, in which Kaikovus' work "Nightmare" describes a spiritually mature generation the idea of education was studied, and the issues of forming positive qualities and qualities of a person were highlighted.